Development of a Computer-Aided Assistance for the Maintenance of an Energy Management System According to DIN EN ISO 50001 - Gerrit Schutz (2019)
The purpose of this thesis is to create a software-based solution to manage effectively an energy management system, instead of using nonstandard proprietary software to do the same. In the offered solution, the open source JEVis System is used as a data storage as well as an interface: the presentation is made on a browser using HTML and JavaScript.